FINITE ELEMENT METHOD FOR SOLVING EIGENVALUE PROBLEM - WIRAWAN (NIM : 20914012), RANGGA
In this Thesis, Eigenvalue problems derived from Diffusion Equation with separation variable method is studied. The Finite Element Method is then applied to construct Stiffness and Mass Matrices so that the Generalized Matrix Eigenvalue is obtained using Cholesky Factorization, The generalized eigenvalue problem is reduced into an Ordinary Eigenvalue problem. The Smallest Eigenvalue of the resulted matrix is found by The Invers Power Method.